Audit committee and the amendments of quarterly financial reports among Malaysian companies - Ku Nor Izah Ku Ismail,; Sharifah Asmawati Syed Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This paper examines the association between audit committee characteristics (independence,expertise and activities)and the amendments of quarterly financial reports of Malaysian companies. Control variables, namely size of board of directors,size of company, profitability and auditor are also included in this study. In this study, earch of the 63 sampled companies that amended their quarterly reports in 2005 is matched with a company that did not make any amendments. Results of the regression test indicate that companies having audit committees with two or more financial experts are less likesly to amend their quarterly reports although other variables (except for auditor) appear to have anegative association with amendments,statistically the association is insignificant. This study also observed taht most of the amendment are due to oversight, mathematical mistakes and typographical errors. The findings suggest thet to be effective, audit committees should have more than one financial expert.